A tira cômica no livro didático de língua portuguesa e no caderno de apoio da Prefeitura de São Paulo - Silva, Yara Dias da [UNIFESP] (2016)
This dissertation aims to study the comic strips in the 2009 edition of the textbook Portuguese: the art of the word and the second chapter of the Portuguese Language schoolbook for learning and support, both of them are destined for the seventh grade of elementary school. Our proposal is to check how these strips contributes to the reading of multimodal genres process to be performed by the student, which will be done through analysis of the proposed activities in these two publications. To approach this proposal, we will: 1) verify how the strips are taken in the teaching materials used in classrooms of São Paulo; 2) evaluate how the process of reading them in these materials is; 3) observe how is the dialogue between these educational materials and official documents of education in the country. We are based on the concepts of linguistics Textual, which are articulated with theoretical assumptions related to comics and based on research and official documents on education in Brazil, we seek to carry out an analysis of the language within the school context. From Linguistics Textual, we rely on the text concepts, discourse object, inference, previous knowledge (KOCH, 2009, 2013) and multimodality (Kress, Van Leeuwen, 2001). To regard the comics, we based on hipergenre settings (RAMOS, 2011; MAINGUENEAU, 2006, 2015), and constituent elements of language (RAMOS, 2014th; Cagnin, 1975). From Official documents, we will review the National Curriculum Parameters (PCN) in relation to the reading aspect. The Curriculum Guidelines and Proposal of Portuguese Language learning expectations of elementary school, in addition to reading, we selected what is presented as expected to be achieved, specifically in reading the comics. We also seek to bring and analyze what is said in both materials on the role of the professor of Portuguese language in the classroom. We also focus on the Law for Education Basis in Brazil (LDB 9.394 / 1996), we rely on the fact that it has effected a change in the conception of language and teaching of Portuguese language, which generated a change in teaching materials. Regarding to the design of textbook Portuguese, we are based on Bunzen (2005) and Mendonça (2012). To understand the way of textbook in Brazil, we will rely on Dias (2010), Oliveira (1984), Rojo & Batista (2003), Jury & Rojo (2006), in addition to sites FNDE (National Fund for Education Development) and ABRELIVOS (Brazilian Association of School Books Publishers). From the analysis it was found that activities were presented that is not reduced to linguistic analysis, however, most of the exercises was the comics, specifically the comic strips of marginalized way, always with the grammatical content learning objective, without being taken into consideration the direction of the strips, often unsuitable for the public to which the material is intended. Such an approach proves what they say the National Curriculum Parameters, under which the only aimed at checking the grammatical content work is exceeded by not allowing the formation of a critical citizen. Thus, our aim was to show that there are ways to propose exercises that explore the articulation of linguistic elements to visual, reading these multimodal texts, contributing greatly to the reader student education, assisting him in building critical awareness about what runs through your reality, thus allowing the school function is fulfilled and to form effectively a citizen, as established by PCN. The approach of comics focused on the production level as well as in non-verbal elements allied to verbal, can instigate the student's interest and become a powerful resource for the teacher, as exercising the work with texts composed by more than one method, which require joint information, activation of prior knowledge, inferences, exchange experience with colleagues, to be built one of the many possible meanings. Thus, it is possible to contribute in a significant way to the development of the construction process of meaning of these texts, helping students develop their reading capacity.